Finding One S Position in Society: A Vignette-Based Survey [Encontrar la Posición de Uno Mismo en la Sociedad: Una Encuesta Basada en Viñetas] - Valenzuela-Rabi, A (Associacao Nacional de Pos-Graduacao e Pesquisa em Ciencias Sociais - ANPOCS, 2019)
Empirical research in various countries shows that a significant part of the population is subjectively identified with the middle classes. Starting from a classification of people in society developed by individuals themselves, we analyze how they identify with a social position. Our analysis is based on a survey in which the participants were asked to perform a classification game of vignettes representative of people in Chilean society. The survey was applied in Chile in the year 2016 to a sample of 2,000 individuals statistically representative of the population. The results show the criteria that predominate when classifying people in society and what influences the definition of their social position by individuals, who selfidentify mainly with a lower category. © Associacao Nacional de Pos-Graduacao e Pesquisa em Ciencias Sociais - ANPOCS.